Gillies fan flap repair for near total, full thickness defect of lower lip - Aggarwal, Beena; Kumar, Hitesh; Sharma, Prashant; Kaushik, Manish; ., Saurabh (International Surgery Journal, 2018)
Lip is one of the commonest sites of occurrence of squamous cell carcinoma in head and neck region. 90 % of the cases involve lower lip. Higher cumulative exposure of ultraviolet radiations by sun is an attributed risk factor. A large defect left after surgical excision can be covered by various methods. Myo-neurovascular flap used in Gillies fan flap technique is considered better functionally and aesthetically. We report a 70-year-old gentleman who presented with large carcinomatous growth occupying more than 3/4th of lower lip, only leaving commisures free. Edge wedge biopsy revealed it to be squamous cell carcinoma. Excision of tumor was done along with bilateral supra-omohyoid neck dissection and Gillies fan flap repair. Modified Gillies fan flap repair is one of the various techniques which serves to reconstruct large lower lip defects maintaining the vascularity, nerve supply of lip and gives functional, sensate and aesthetic results